APLIKASI SISTEM INVERTER 1 FASA DENGAN KAPASITAS BEBAN 1200 WATT - Suyanto, Muhammad (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2013)
Providers Backup Power Supply for Household Electricity Load In automatic, very necessary as an emergency response efforts in the event of termination of electricity to consumers. So with a backup power supply that has been prepared, the electric lighting in the household is not disrupted. The effort is meant is conducted by making a piece of equipment such as power supply 1 Phase Inverter System Design for Load Capacity 1200 Watt, is a piece of equipment that can serve as a replacement power supply but can work efficiently and save energy. After designing and testing tools execute the inverter, it can be some of the results of the designation gauges recorded and performed calculations. The larger the installed load will produce a greater flow, this caused huge load requires a large current flow. At 50-250 cosQ load close to 1, while the 300-1200Watt load cosQ up and down, this happens when the 300-1200Watt load test, the load used in the form of incandescent bulbs. The voltage on the inverter device is sometimes not reached 220 volts when tested. This is due to the voltage source when the test does not reach the stable, and also due to the greater load at the time of testing with mixed loads. Long period of time of an inverter is able to work depends on the quality of the battery and how to use it.